Comparative framing of the Palestinian-Israeli conflict in newspapers: an analysis of affect - Abdallah ZA Warshagha,; Pei, Soo Ang; Huan, Changpeng (Penerbit Universiti Kebangsaan Malaysia, 2024)
In an era where media warfare parallels armed conflict with immense power to create or challenge narratives and shape public sentiment, this study dissects the journalistic tactics employed in reporting the Palestinian-Israeli conflict by two influential news giants: Al Jazeera English (AJE) and The Washington Post (WP). Based on the Faircloughian socio-dialectical perspective and Martin and White’s (2005) affect subsystem within the appraisal theory, this study investigates how language choices shape meanings, select voices, and perpetuate specific ideologies. The analysis of a corpus of 117 news articles from Al Jazeera English (AJE) and 115 from The Washington Post (WP) reveals that both outlets utilize interpersonal emotions to craft narratives that are more provocative than informative. Essentially, these two news organizations are found to be consciously or subconsciously steering public sentiment, fostering divisive worldviews, and cultivating polarized perspectives. AJE prioritizes narratives that amplify Arab and Muslim perspectives while railing against Israeli occupation and American prejudicial policies. WP, conversely, offers a lens colored by US geopolitical interests, sidelining Arab and Palestinian grievances in the process. Consequently, each outlet’s emotionally charged reporting serves as a tinderbox that inflames public opinion, escalates conflict, and deepens societal fissures. The study underscores the urgent need for journalistic integrity by media professionals and advocates for a shift in conflict reporting that recognizes the consequences of emotion-laden narratives, which negatively impact public discourse and hinder the path toward peaceful resolutions.